Staged Parameter Optimisation for a Robotic Bird Model - Vlot, Sander; Heslinga, Marjolijn; Keulen, Bart; Wymenga, Jan (Student Undergraduate Research E-journal!, 2015)
This paper proposes a method to estimate a nonlinear mathematical model describing the dynamic behaviour of a robotic bird. Established knowledge on aircraft modelling and aerodynamics is used to derive an appropriate model structure. A new parameter optimisation method is developed, which consists of experiment design and staged parameter optimisation using datasets from test flights. The modelling method delivers promising results for predicting pitch and yaw of a model aeroplane and can be applied to the Robird when flight data become available.